Bridging Sex-Specific Differences in the CAR-Mediated Hepatocarcinogenesis of Nitrapyrin Using Molecular and Apical Endpoints - Murphy, Lynea; LeBaron, Matthew J.; Johnson, Kamin; Rasoulpour, Reza J.; Wang, Xiujuan; LaRocca, Jessica (Frontiers in Toxicology, 2021)
Nitrapyrin, a nitrification inhibitor, produces liver tumors in B6C3F1 mice. In a 2-year oncogenicity study, increased incidence of mice with hepatocellular tumors was observed following exposure to 125 (females only) or 250 mg/kg/day (males and females) nitrapyrin in the diet. Previous data was generated in male mice to support a mode-of-action (MoA) characterized by constitutive androstane receptor (CAR) nuclear receptor (NR) activation, increased hepatocellular proliferation, and subsequent hepatocellular foci and tumor formation. Uncertainty as to the relevance of this MoA for females remained given the increased sensitivity to tumor formation in female mice. A targeted MoA study was conducted to evaluate CAR activation and hepatic responses in female mice treated with the female carcinogenic dose of nitrapyrin for 4 days. Nitrapyrin induced a treatment-related increase in hepatocellular hypertrophy and hepatocellular proliferation. Nitrapyrin also induced a dose-related increase in the Cyp2b10/CAR-associated transcript and liver weights. Nitrapyrin-induced liver weights and Cyp2b10 gene expression for both males and females were compared to data generated from three other established CAR activators; methyl isobutyl ketone, phenobarbital, and sulfoxaflor. The response observed in female mice following exposure to nitrapyrin was within range of the degree of change observed in mice following exposure to tumorigenic doses of other CAR activators. Consistent with the liver MoA in male mice, these data support a CAR-mediated mode of action for nitrapyrin-induced liver tumors in female mice, with the understanding that a focused approach minimizing animal use can bridge male and female datasets when sex-specific carcinogenic differences are observed.